2014
DOI: 10.1021/jp507670c
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Properties of Fully Condensed Functional Silsesquioxane: A Langmuir Monolayer Study

Abstract: We have studied interfacial properties of fully condensed octakis[{2-(3,4-epoxy­cyclo­hexyl)­etyl}­dimethyl­silyloxy]­octa­silsesquioxane (OE-POSS). The surface pressure–area isotherm obtained in a Langmuir trough together with Brewster angle microscopy indicated formation of a stable, homogeneous liquid-like monolayer. For low molecular areas, the monolayer undergoes a stepwise collapse showing unusual multilayer morphology. A collapse mechanism is proposed to be a consequence of progressive decrease in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The result indicates that pDDA is a good amphiphilic polymer to stabilize the monolayer. The limiting molecular occupied area ( A unit ), compression modulus ( C s –1 ), , and characteristic surface pressure (π*: defined as the surface pressure π when C s –1 reached the maximum point) were calculated from the π– A and C s –1 – A isotherms (Figures and S1). A unit was determined by extrapolating the linear portion of the condensed state in the π– A isotherm to zero pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The result indicates that pDDA is a good amphiphilic polymer to stabilize the monolayer. The limiting molecular occupied area ( A unit ), compression modulus ( C s –1 ), , and characteristic surface pressure (π*: defined as the surface pressure π when C s –1 reached the maximum point) were calculated from the π– A and C s –1 – A isotherms (Figures and S1). A unit was determined by extrapolating the linear portion of the condensed state in the π– A isotherm to zero pressure.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of E ′′ to E ′ is defined as the tangent of the loss angle, tan θ , where θ is the phase shift between the imaginary component and the real component of the dilatational modulus. A value of tan θ lower than 1 implies elastic properties of the monolayer, whereas a value of tan θ greater than 1 reveals a more viscous character …”
Section: Resultsmentioning
confidence: 99%
“…[37,39] The surface viscoelastic properties of the POSS monolayers spread on the air-water interface, as af unctiono ft he frequency of oscillations, were investigated at different surface states characterized by given values of the surface pressure. For ap erfectly viscousm onolayer,t he real part is equal to zero, whereas for ap erfectly elastic one, the imaginary parti sz ero.…”
Section: Peg-poss (2)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014 we reported the rst fully-condensed, multifunctional POSS, octakis[{2-(3,4epoxycyclohexyl)etyl}dimethylsilyloxy]octasilsesqui-oxane that forms stable Langmuir lm. 21 Recently, Paczesny et al demonstrated another fully-condensed, monofunctional POSS compounds bearing glycerol unit, maleamic acid and amino group which behave like typical amphiphiles. 22 On the other hand, POSS, especially uorinated derivatives, were recognized as excellent materials for fabrication of water-repellent surfaces.…”
Section: Introductionmentioning
confidence: 99%